Influence of storage and temperature treatment on nutritional value of wheat for poultry - Masey O'Neill, Helen Victoria (2008)
Worldwide production of wheat in 2007 was 787 million (IGC 2008). Due to its importance in the world commodity market, there has been much research into the potential problems of weather damage to wheat, particularly with reference to bread making. The current project aimed to address three major research areas. Firstly, the effects of heat treatment in relation to the nutritional value of weather damaged wheat were investigated. It appears that drying at 100°C may increase Coefficient of Apparent Digestibility of starch (CAD). Some flour samples that were heated to 100°C failed to demonstrate expected hydration properties that would normally be associated with increased digestibility. They also appear to maintain their crystalline order. Therefore, an increase in CAD is not necessarily related to changes in starch structure and is probably more likely due to modification of non-starch components such as protein. A hypothesis is discussed, that proteins may form a film that protects the starch until the protein is digested by endogenous chick proteases. The precise drying temperature is critical, as at 85°C, digestibility may be decreased, possibly due to crystalline perfection. Apparent Metabolisable Energy (AME) did not follow starch digestibility. Secondly, it was hypothesised that the Rapid Visco Analyser (RVA) may be able to quantify amylase activity and predict nutritional value of wheat samples. Interestingly, unexpectedly high levels of amylase were observed in some wheat samples. This activity remained despite two years in ambient storage and temperature treatment of up to 100°C. These high levels of amylase activity did not appear to affect CAD, presumably due to deactivation in the acidic conditions of the proventriculus. There were some highly significant relationships between in vivo parameters and in vitro RVA parameters, particularly between Peak Viscosity (with an amylase inhibitor) and Coefficient of Duodenal Digestibility or AME (P<O.OOI in both cases). This suggests there is potential for the RV A to indicate nutritional value. Lastly, the nutritional value of wheat after storage for up to four months was investigated. There was no significant difference in AME, CAD or FI.